The Lives of The Sibolga Community During the Monetary Crisis in 1998 - Situmorang, Gerardus Monang; Simanjuntak, Peninna; Junaidi, Junaidi (Prodi Ilmu Sejarah, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Jambi, 2025)
This research aims to reveal the living conditions of the Sibolga community during the monetary crisis that hit Indonesia in 1998. This period also marked a fundamental change from the Suharto regime (new order) to the reformation period. This research seeks to reveal the economic conditions of the community before the monetary crisis, the survival strategies of the community when the monetary crisis hit, and the impact of the crisis on the economy of the Sibolga community. This research uses the historical method with four phases: heuristics, verification, interpretation, and historiography. Information was obtained from interviews, official government documents, newspapers, research reports and books. The results showed that the economic conditions of the Sibolga community during the monetary crisis experienced a decline, while the prices of basic goods continued to increase, so that people could not fulfil their basic needs because people's purchasing power decreased. In this situation, the community of Sibolga tried to find additional work, because they could not rely on just one main job whose results were insufficient for their needs. In addition, the city government also provides staple food assistance and education funding for those who are struggling.